Artificial nap leather

JP7638214B2Active Publication Date: 2025-03-03KURARAY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021545498
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-17
Filing Date
2020-09-03
Publication Date
2025-03-03
Estimated Expiration
2040-09-03

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、優美な立毛の外観と高い耐摩耗性と高い摩擦堅牢性と柔軟な風合いとを兼ね備えた立毛人工皮革が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638214000004
    Figure 0007638214000004
  • Figure 0007638214000005
    Figure 0007638214000005
  • Figure 0007638214000006
    Figure 0007638214000006
Patent Text Reader

Abstract

This napped artificial leather comprises a nonwoven fabric that is an entangled body of ultrafine fibers and a polymer elastic body that is provided in the nonwoven fabric, and has, on at least one surface, a napped surface provided by napping the ultrafine fibers. The ultrafine fibers have a fineness of not more than 0.5 dtex and a tensile strength of 6-9 mN, and a plurality of ultrafine fibers form a fiber bundle. In a region excluding a surface layer, the ultrafine fibers forming a fiber bundle are not constrained by the polymer elastic body. The napped artificial leather has a polymer elastic body content of 16-40% and an apparent density of at least 0.38 g / cm3.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a napped artificial leather which is preferably used as a surface material for clothing, shoes, furniture, car seats, miscellaneous goods, etc. [Background technology]

[0002] Conventionally, there are known napped artificial leathers such as suede-like artificial leathers and nubuck-like artificial leathers. The napped artificial leathers have a napped surface containing napped fibers, which is formed by nap-raising one side of a nonwoven fabric impregnated with a polymeric elastomer. Abrasion resistance is required for such napped artificial leathers.

[0003] Regarding the abrasion resistance of napped artificial leather, for example, Patent Document 1 listed below discloses a suede-like artificial leather obtained by applying a polymer elastomer to a leather-like sheet material consisting of ultrafine fibers and a polymer elastomer, extracting one component of the mixed fibers after applying the polymer elastomer again, and then binding the ultrafine fibers that form the fiber bundles with the polymer elastomer.

[0004] In addition, the following Patent Document 2 discloses an artificial leather that is flexible and has good abrasion resistance, which is obtained by applying a treatment liquid in which inorganic salts are dissolved and mixed in an aqueous polyurethane emulsion having an average emulsion particle size of 0.1 to 2.0 μm to a nonwoven sheet-like material that includes a fiber layer made of ultrafine fibers having a single fiber fineness of 0.5 denier or less as a surface fiber layer, and then drying the material by heating.

[0005] Furthermore, the following Patent Document 3 discloses an artificial leather obtained by preparing an artificial leather substrate, swelling a polymeric elastomer with a solvent, and then compressing the polymeric elastomer to bond ultrafine fibers and the polymeric elastomer.

[0006] Furthermore, the following Patent Document 4 discloses a napped artificial leather comprising a nonwoven fabric having entangled fibers and a polymer elastomer, in which the 100% modulus (A) of the polymer elastomer and the content (B) of the polymer elastomer satisfy the relational expressions B≧−1.8A+40, A>0.

[0007] Furthermore, the following Patent Document 5 discloses a sheet-like material using a nonwoven fabric mainly made of ultrafine fibers and artificial leather made of an elastic polymer, in which the nonwoven fabric is made of ultrafine long fibers containing polyester as a main component, the polyester contains 1 to 500 ppm of a component derived from 1,2-propanediol, and further has a CV value of 5% or less on the basis weight in the width direction.

[0008] Furthermore, in the case of napped artificial leather, friction of the napped surface can cause the ultrafine fibers to fall out or break, and the ultrafine fibers that are free on the surface can become entangled when further rubbed, resulting in the problem of pilling, which is a phenomenon in which small, spherical lumps like fuzz balls form.

[0009] As a method for suppressing the occurrence of pilling in raised-pile artificial leather, there are known methods for increasing the degree of entanglement of the ultrafine fibers forming the nonwoven fabric, increasing the content of the polymeric elastomer impregnated in the nonwoven fabric, or foaming the polymeric elastomer to restrain the ultrafine fibers, or weakening the strength of the ultrafine fibers to make them easier to break. However, when the content of the polymeric elastomer impregnated in the nonwoven fabric is increased to increase the restraint of the ultrafine fibers, there is a problem that the feel becomes hard, and when the polymeric elastomer is foamed to increase the effective volume and to increase the restraint force, the manufacturing cost increases. In addition, when the strength of the ultrafine fibers is weakened to make them easier to break, pilling is less likely to occur, but there is a problem that abrasion resistance is reduced.

[0010] Regarding napped artificial leather with excellent pilling resistance, the following Patent Document 6 discloses a method for increasing the degree of entanglement of ultrafine fibers and peeling the napped surface, the L measured with a spectrophotometer on the napped surface before and after a surface peeling treatment. * a * b * Based on the color system L * The present invention discloses a napped artificial leather having a value change rate of +9% or less.

[0011] As a technique for improving the abrasion resistance of napped artificial leather, for example, Patent Document 7 listed below discloses napped artificial leather in which a polymeric elastomer obtained from an aqueous dispersion of a polymeric elastomer is present at and near the base of the nap. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Japanese Patent Application Publication No. 51-75178 [Patent Document 2] Japanese Patent Application Publication No. 06-316877 [Patent Document 3] JP 2001-81677 A [Patent Document 4] WO2019 / 058924 Brochure [Patent Document 5] JP 2019-26996 A [Patent Document 6] JP 2017-106127 A [Patent Document 7] JP 2011-74541 A Summary of the Invention [Problem to be solved by the invention]

[0013] The suede-like artificial leather disclosed in Patent Document 1 has improved abrasion resistance, but has a problem of hard texture because the polymer elastomer restrains the ultrafine fibers. The artificial leather disclosed in Patent Document 2 also has improved abrasion resistance, but has a problem of hard texture. The artificial leather disclosed in Patent Document 3 also has a problem of hard texture when the abrasion resistance is sufficiently improved because the polymer elastomer restrains the ultrafine fibers. The artificial leather disclosed in Patent Document 4 also has improved abrasion resistance, but has a problem of insufficient improvement in friction fastness affected by the falling off of ultrafine fibers. The artificial leather disclosed in Patent Document 5 also has improved abrasion resistance because the polymer elastomer is added after ultrafine fibers are formed from islands-in-the-sea composite fibers, but has a problem of hard texture because the polymer elastomer restrains the ultrafine fibers.

[0014] In addition, the napped artificial leather disclosed in Patent Document 6, in which the entanglement degree of ultrafine fibers is increased, has improved pilling resistance but has a problem of hard texture. In addition, the napped artificial leather disclosed in Patent Document 7 also has excellent abrasion resistance but has a problem of hard texture because the polymeric elastomer restricts the ultrafine fibers.

[0015] An object of the present invention is to provide a napped artificial leather that combines an elegant napped appearance with high abrasion resistance, high friction resistance, and a soft feel. [Means for solving the problem]

[0016] One aspect of the present invention is a raised artificial leather comprising a nonwoven fabric which is an entanglement of ultrafine fibers and a polymeric elastomer applied to the nonwoven fabric, and having at least one surface on which the ultrafine fibers are raised, the ultrafine fibers having a fineness of 0.15 to 0.5 dtex and a tensile strength of Force A (mN) is 6.5 to 8 m N ultrafine fibers, a plurality of ultrafine fibers form fiber bundles, and in a region other than the surface layer portion, the ultrafine fibers forming the fiber bundles are not bound by a polymer elastomer, and the content of the polymer elastomer is The sum B (mass%) is 3.125×A≦B≦4 0 mass % formula is satisfied, Apparent density is 0.3 8~0.48g / cm 3 inThe napped artificial leather is a type of raised nap artificial leather. Such a raised nap artificial leather has an elegant appearance of raised nap, high abrasion resistance, high friction resistance, and soft texture. The ultrafine fibers are not bound by the polymer elastomer, which means that the ultrafine fibers forming the nonwoven fabric form a fiber bundle formed by removing the sea component from the islands-in-sea type composite fiber, and that the fibers are not fixed to each other by the polymer elastomer in the ultrafine fiber bundle formed by removing the sea component from the islands-in-sea type composite fiber. When the fibers are not fixed to each other by the polymer elastomer in the ultrafine fiber bundle, the ultrafine fibers are not bound to each other by the polymer elastomer even if the polymer elastomer is fixed to a part of the outer periphery of the ultrafine fiber bundle.

[0017] The tensile strength of the ultrafine fibers is in the range of 6.5 to 8 mN (mN), and the apparent density of the raised nap artificial leather is 0.38 to 0.48 g / cm 3 The content ratio B of the polymer elastomer is 3.125×A≦ The formula for B≦40 Fulfilled vinegar. According to such a napped artificial leather, a napped artificial leather further having high pilling resistance can be obtained.

[0018] In addition, it is preferable that the polymer elastomer is a solvent-based polyurethane, because even if the amount of the polymer elastomer is increased, the polymer elastomer and the ultrafine fibers can be appropriately dissociated, making it easy to obtain a napped artificial leather with a soft feel.

[0019] The expansion ratio of the polymeric elastomer is preferably 0 to 5% by mass. When the polymeric elastomer is expanded at a high expansion ratio, the volume of the polymeric elastomer increases and surrounds the ultrafine fibers, making it difficult for the ultrafine fibers to pass through, improving pilling resistance. However, in order to expand the polymeric elastomer at a high expansion ratio, it is necessary to adjust additives or increase the solidification temperature, which is undesirable since it tends to increase the production cost.

[0020] In addition, it is preferable that a portion of the polymer elastomer present in the surface layer portion is fixed near the base of the raised ultrafine fibers, since this makes it difficult for the raised fibers on the raised surface to come loose and also makes it difficult for the raised fibers to be raised by friction, thereby improving the appearance quality.

[0021] In addition, the ultrafine fibers are preferably ultrafine fibers formed by dissolving and removing the sea component from islands-in-sea type composite fibers with an organic solvent, from the viewpoint of facilitating the production of the napped artificial leather described above.

[0022] In addition, the nonwoven fabric is preferably a spunbond nonwoven fabric containing ultrafine long fibers, since this makes it easier to obtain the napped artificial leather described above. Effect of the Invention

[0023] According to the present invention, it is possible to obtain a napped artificial leather that combines an elegant napped appearance with high abrasion resistance, high friction resistance, and a soft feel. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is an explanatory diagram for explaining a method for measuring the tensile strength of ultrafine fibers. [Diagram 2] FIG. 2 is a graph plotting the content ratio of polymer elastomer (B) relative to the tensile strength (A) of ultrafine fibers contained in the napped artificial leathers obtained in Examples 7-20. [Diagram 3] FIG. 3 is a graph plotting the content ratio of polymer elastomer (B) relative to the tensile strength (A) of ultrafine fibers contained in the raised artificial leathers obtained in Examples 21 to 33 and Comparative Examples 8 to 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The napped artificial leather of the present embodiment includes a nonwoven fabric which is an entanglement of ultrafine fibers and a polymeric elastomer applied to the nonwoven fabric, and has at least one napped surface on which the ultrafine fibers are napped. The ultrafine fibers have a fineness of 0.15 to 0.5 dtex and a tensile strength of 10 ... Force A (mN) is 6.5 to 8 m N ultrafine fibers, a plurality of ultrafine fibers form fiber bundles, and in a region other than the surface layer portion, the ultrafine fibers forming the fiber bundles are not bound by a polymer elastomer, and the content of the polymer elastomer is The sum B (mass%) is 3.125×A≦B≦4 0 mass % formula is satisfied, Apparent density is 0.3 8~0.48g / cm 3 in The napped artificial leather of the present embodiment will be described in detail below while explaining an example of a manufacturing method thereof.

[0026] A nonwoven fabric that is an entanglement of ultrafine fibers is a nonwoven fabric of ultrafine fiber bundles in which a plurality of ultrafine fibers form fiber bundles. Such a nonwoven fabric can be obtained by entangling islands-in-the-sea (matrix-domain) composite fibers and then subjecting them to an ultrafine fiber processing.

[0027] A method for producing a nonwoven fabric which is an entangled body of ultrafine fibers includes a method in which islands-in-sea type composite fibers are melt-spun to produce a web, the web is entangled, and then the sea part is selectively removed from the islands-in-sea type composite fibers to form ultrafine fibers. In any step from removing the sea part of the islands-in-sea type composite fibers to forming the ultrafine fibers, the islands-in-sea type composite fibers may be densified by performing a fiber shrinkage treatment such as a heat shrinkage treatment using water vapor, hot water, or dry heat.

[0028] As a method for producing a web, there may be mentioned a method in which islands-in-sea type composite fibers spun by a spunbonding method are collected on a net without being cut to form a web of long fibers. Alternatively, as another method, a web of short fibers may be formed by carding the raw staple of islands-in-sea type composite fibers obtained by crimping and cutting melt-spun islands-in-sea type composite fibers. Among these, it is particularly preferable to use a web of long fibers derived from islands-in-sea type composite fibers spun by a spunbonding method, because the entanglement state can be easily adjusted and a high sense of fullness can be obtained. The formed web may be subjected to a fusion treatment to impart shape stability. Below, an example in which long fibers of islands-in-sea type composite fibers are used will be described in detail as a typical example.

[0029] Here, the term "long fibers" means continuous fibers that are not short fibers that are intentionally cut after spinning. More specifically, it means filaments or continuous fibers that are not short fibers that are intentionally cut to have a fiber length of about 3 to 80 mm, for example. In order to form long fibers, the fiber length of the islands-in-sea type composite fiber before being made into ultrafine fibers is preferably 100 mm or more, and may be several meters, several hundred meters, several kilometers, or even longer, as long as it is technically possible to produce the fibers and the fibers are not inevitably cut during the production process. Here, needle punching during entanglement or surface buffing may inevitably cut a part of the long fibers to become short fibers during the production process.

[0030] Examples of the resins of the island components that become the ultrafine fibers include modified PET such as polyethylene terephthalate (PET), isophthalic acid modified PET, sulfoisophthalic acid modified PET, and cationic dye dyeable PET, aromatic polyesters such as polybutylene terephthalate and polyhexamethylene terephthalate, aliphatic polyesters such as polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, and polyhydroxybutyrate-polyhydroxyvalerate resin, nylons such as nylon 6, nylon 66, nylon 10, nylon 11, nylon 12, and nylon 6-12, and polyolefins such as polypropylene, polyethylene, polybutene, polymethylpentene, and chlorine-based polyolefins. The modified PET is a PET in which at least a part of the ester-forming dicarboxylic acid monomer units or diol monomer units of unmodified PET are replaced with substitutable monomer units. Specific examples of modified monomer units substituting dicarboxylic acid monomer units include units derived from isophthalic acid, sodium sulfoisophthalic acid, sodium sulfonaphthalenedicarboxylic acid, adipic acid, etc., which substitute terephthalic acid units. Specific examples of modified monomer units substituting diol monomer units include units derived from diols such as butanediol and hexanediol, which substitute ethylene glycol units.

[0031] In addition, in the islands-in-the-sea type composite fiber, for example, dark color pigments such as carbon black, white pigments such as zinc oxide, white lead, lithopone, titanium dioxide, precipitated barium sulfate, and baryte powder, weathering agents, fungicides, hydrolysis inhibitors, lubricants, fine particles, friction resistance adjusters, and the like may be blended as necessary within the range that does not impair the effects of the present invention.

[0032] Fineness 0.15~0.5dtex and tensile strength 6.5~8m The following method can be exemplified for forming a nonwoven fabric containing fiber bundles of ultrafine fibers of type N. One method is to select a thermoplastic resin having a relatively high intrinsic viscosity and melting point as the island component of the islands-in-sea type composite fiber for producing ultrafine fibers, select a thermoplastic resin that solidifies slower than the island component as the sea component, and apply a spinning draft (discharge speed / spinning speed) of a certain level or more to the island component to perform melt spinning.

[0033] The intrinsic viscosity of the island component resin for obtaining ultrafine fibers is 0.55 to 0.8 dl / g, and further 0.55 to 0.75 dl / g. 6.5~8m If the intrinsic viscosity of the thermoplastic resin for the island component is too low, the tensile strength of the resulting ultrafine fibers tends to be low. If the intrinsic viscosity of the thermoplastic resin for the island component is too high, melt spinning becomes difficult, and the fineness of 0.15 to 0.5 dtex and the tensile strength of the resulting ultrafine fibers tend to be low. 6.5~8m It becomes difficult to obtain ultrafine fibers such as N.

[0034] As the sea component resin to be removed by extraction or decomposition later, a resin having a different solubility or decomposability from the island component resin and low compatibility is used. Such a resin is appropriately selected depending on the type of the island component resin and the manufacturing method. Specific examples include olefin resins such as polyethylene, polypropylene, ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer; resins that are soluble in organic solvents and can be dissolved and removed by organic solvents such as polystyrene, styrene-acrylic copolymer, and styrene-ethylene copolymer; and water-soluble resins such as water-soluble polyvinyl alcohol. Among these, resins that can be dissolved and removed by organic solvents are preferred, and polyethylene is particularly preferred, because even island component resins with high intrinsic viscosity can be melt-spun.

[0035] A web of islands-in-sea type composite fibers can be produced by a spunbonding method in which a composite spinning die having a large number of nozzle holes arranged in a predetermined pattern is used, molten strands of islands-in-sea type composite fibers are continuously discharged from the composite spinning die at a predetermined discharge speed from a spinning nozzle, and the strands are stretched while being cooled using a high-speed air stream, and then deposited on a moving net in the form of a conveyor belt. The web deposited on the net may be heat-pressed to impart shape stability.

[0036] The number of island components that become ultrafine fibers in the cross section of the islands-in-sea type composite fiber is preferably 5 to 200, more preferably 10 to 50, and even more preferably 10 to 30, from the viewpoint of easily forming fiber bundles of ultrafine fibers having appropriate voids.

[0037] In this case, the melt spinning conditions for the islands-in-sea type composite fiber are preferably as follows: The discharge speed of the molten resin discharged from one hole of the spinning nozzle is A (g / min), and the melt specific gravity of the resin is B (g / cm 3 ), the area of ​​one hole is C (mm 2 ), and the spinning speed is D (m / min). The conditions set so that the spinning draft calculated by the following formula is in the range of 200 to 500, and further 250 to 400, are the conditions for a fineness of 0.15 to 0.5 dtex and a tensile strength of 6.5~8m This is preferred because it is easy to obtain ultrafine fibers such as N. Spinning draft = D / (A / B / C)

[0038] The entanglement method may be the following. For example, a method may be used in which a web is laminated in a thickness direction using a cross wrapper or the like, and then needle punched or high-pressure water jet treatment is performed under conditions in which at least one barb penetrates from both sides simultaneously or alternately. The punch density of the needle punch treatment is 1500 to 5500 punches / cm. 2 , and even 2000~5000 punches / cm 2 It is preferable that the punch density is about that level because high abrasion resistance is easily obtained. If the punch density is too low, the abrasion resistance tends to decrease, and if the punch density is too high, the fibers tend to be cut and the degree of entanglement tends to decrease.

[0039] In addition, an oil agent or an antistatic agent may be applied to the web at any stage from the spinning process of the islands-in-sea type composite fiber to the entanglement treatment. Furthermore, if necessary, the web may be immersed in hot water at about 70 to 150°C for shrinkage treatment to make the entanglement state of the web dense in advance.

[0040] The weight of the entangled web obtained by entangling the webs is 100 to 2000 g / m 2 It is preferable that the fiber density is in the range of about 100°C to 150°C. Furthermore, the entangled web may be heat-shrunk as necessary to further increase the fiber density and the degree of entanglement. In addition, in order to further densify the entangled web densified by the heat shrinkage treatment, fix the shape of the entangled web, smooth the surface, etc., the fiber density may be further increased by pressing the entangled web heated to or above the softening point of the resin constituting the fibers with a cooling roll set to a surface temperature below the softening point, as necessary. In particular, pressing with a cooling roll set to a surface temperature 30°C or more lower than the softening point is particularly preferable because the surface becomes smoother.

[0041] In the manufacture of napped artificial leather, in order to provide shape stability and a solid feel, a polymeric elastomer is impregnated into an entangled web obtained by entangling islands-in-sea composite fibers before the sea component is removed. By impregnating an entangled web obtained by entangling islands-in-sea composite fibers before the sea component is removed with a polymeric elastomer in this manner, gaps are formed between the ultrafine fibers that form the fiber bundles after the sea component is removed, which are formed by removing the sea component. As a result, the ultrafine fibers inside the fiber bundles are not bound by the polymeric elastomer, and a napped artificial leather having a soft texture is obtained. Note that, when a polymeric elastomer is impregnated into a nonwoven fabric of ultrafine fibers that form the fiber bundles after the sea component is removed from the islands-in-sea composite fibers, the polymeric elastomer penetrates into the gaps in the fiber bundles, and the ultrafine fibers inside the fiber bundles that form the fiber bundles are bound by the polymeric elastomer, thereby obtaining a napped artificial leather with a hard texture.

[0042] Specific examples of the polymeric elastomer include polyurethane, acrylonitrile elastomer, olefin elastomer, polyester elastomer, polyamide elastomer, and acrylic elastomer. Among these, polyurethane is particularly preferred. Specific examples of polyurethane include polycarbonate urethane, polyether urethane, polyester urethane, polyether ester urethane, polyether carbonate urethane, and polyester carbonate urethane. The polyurethane may be a polyurethane (solvent-based polyurethane) obtained by impregnating a nonwoven fabric with a solution of polyurethane dissolved in a solvent such as N,N-dimethylformamide (DMF) and then wet-coagulating the polyurethane to solidify it, or a polyurethane (water-based polyurethane) obtained by impregnating a nonwoven fabric with an emulsion of polyurethane dispersed in water and then drying and solidifying it. Among these, solvent-based polyurethane is particularly preferred because it is easy to obtain a raised-pile artificial leather having a soft texture by appropriately dissociating the polyurethane and ultrafine fibers even if the amount of polyurethane is increased.

[0043] The polymer elastomer may contain colorants such as pigments, e.g., carbon black, and dyes, coagulation regulators, antioxidants, ultraviolet absorbers, fluorescent agents, antifungal agents, penetrating agents, defoamers, lubricants, water repellents, oil repellents, thickeners, bulking agents, hardening accelerators, foaming agents, water-soluble polymer compounds, e.g., polyvinyl alcohol and carboxymethyl cellulose, inorganic fine particles, and conductive agents, within the scope of the invention.

[0044] The content of the polymeric elastomer impregnated in the napped artificial leather is 16 to 40% by mass. By including the polymeric elastomer in such a ratio, it is possible to obtain a napped artificial leather having an excellent balance between abrasion resistance and a supple feel.

[0045] The polymer elastomer preferably has an expansion ratio in the range of 0 to 5% by mass. When the polymer elastomer is expanded at a high expansion ratio, the polymer elastomer surrounds the ultrafine fibers, making it difficult for the yarn to come out of the fibers, and improving pilling resistance, but this tends to increase production costs due to the need to adjust additives and increase the solidification temperature.

[0046] By removing the sea part resin from the nonwoven fabric in which islands-in-sea type composite fibers are entangled, an artificial leather base can be obtained that includes a nonwoven fabric in which ultrafine fibers forming fiber bundles are not bound by a polymeric elastomer, and a polymeric elastomer impregnated into the nonwoven fabric. The method for removing the sea part resin from islands-in-sea type composite fibers is not particularly limited to any conventional method for forming ultrafine fibers, such as treating a nonwoven fabric in which islands-in-sea type composite fibers are entangled with a solvent or decomposing agent that can selectively remove only the sea part resin.

[0047] The artificial leather substrate thus obtained may be sliced ​​to a predetermined thickness, if necessary. The basis weight of the artificial leather substrate thus obtained is 140 to 3000 g / m 2 , and even 200 to 2000 g / m 2 It is preferable that:

[0048] Then, by buffing one or both sides of the artificial leather substrate, which is a nonwoven fabric of ultrafine fibers impregnated with a polymeric elastomer, a napped artificial leather substrate having a napped surface with the fibers of the surface layer is obtained. Buffing is preferably performed using sandpaper or emery paper of about 120 to 600, more preferably about 320 to 600. In this way, a napped artificial leather substrate having a napped surface with the fibers of the surface layer on one or both sides is obtained.

[0049] In addition, in order to improve the appearance quality by making it difficult for the raised ultrafine fibers on the raised surface to slip out and difficult for the raised ultrafine fibers to be raised by friction, the raised surface of the raised artificial leather substrate may be gravure coated with a solvent that swells or dissolves only the polymeric elastomer but does not dissolve the ultrafine fibers, thereby fixing the ultrafine fiber bundles with the polymeric elastomer. By applying the above-mentioned solvent to the raised surface of the raised artificial leather substrate, the polymeric elastomer around the ultrafine fiber bundles swells or dissolves, and the polymeric elastomer penetrates to fill the gaps in the ultrafine fiber bundles. As the solvent, a solvent that does not dissolve ultrafine fibers made of polyester, polyamide, etc. but swells or dissolves only the polymeric elastomer is selected. Specifically, for example, a mixed solvent of a good solvent and a solvent with a low dissolving ability for the polymeric elastomer is used, and the degree of adhesion between the polymeric elastomer and the ultrafine fibers can be controlled by adjusting the ratio of the good solvent and the solvent with a low dissolving ability.

[0050] For example, when the polymeric elastomer is polyurethane, a mixture of dimethylformamide (hereinafter DMF) or tetrahydrofuran (hereinafter THF) as a good solvent and acetone, toluene, cyclohexanone, ethyl acetate, butyl acetate, etc., which have low dissolving power, in any ratio is used. The mixing ratio of the good solvent to the solvent with low dissolving power is appropriately selected within the range of 10:90 to 90:10 by weight. The temperature of the solvent during application is preferably within the range of 10 to 60°C.

[0051] A polymeric elastomer may be further applied to locally fix the vicinity of the root of the raised ultrafine fiber. Specifically, for example, a solution or emulsion containing the polymeric elastomer is applied to the napped surface, and then the polymeric elastomer is solidified by drying. By applying a polymeric elastomer to locally fix the vicinity of the root of the raised ultrafine fiber present on the napped surface, the vicinity of the root of the fiber present on the napped surface is restrained by the polymeric elastomer, making it difficult for the ultrafine fiber to slip through. Specific examples of the polymeric elastomer applied to the napped surface include those mentioned above. The amount of the polymeric elastomer applied to the napped surface is 1 to 10 g / m 2 , and even 2 to 8 g / m 2 is preferable because it is possible to firmly fix the vicinity of the roots of the ultrafine fibers without making the nap surface too hard.

[0052] The fact that the ultrafine fibers are fixed with the polymeric elastomer means that the polymeric elastomer is fixed so as to restrain the ultrafine fibers when the cross section of the napped artificial leather in the thickness direction is observed with a scanning electron microscope. The surface layer portion means a region to which the polymeric elastomer is locally fixed near the base of the ultrafine fibers, and specifically, for example, a region that is 10% or less, or even 5% or less, in the thickness direction from the base of the nap, relative to the entire thickness of the napped artificial leather. The entire thickness of the napped artificial leather means the thickness excluding the nap.

[0053] The napped artificial leather substrate having a napped surface may be subjected to a shrinking process or a kneading softening process to impart flexibility in order to adjust the texture, or may be subjected to finishing processes such as reverse seal brushing, antifouling, hydrophilic treatment, lubricant treatment, softener treatment, antioxidant treatment, ultraviolet absorber treatment, fluorescent agent treatment, and flame retardant treatment.

[0054] The raised artificial leather substrate having a raised surface is dyed to be finished into raised artificial leather. The dye is appropriately selected depending on the type of ultrafine fiber. For example, when the ultrafine fiber is formed of a polyester resin, it is preferable to dye it with a disperse dye or a cationic dye. Specific examples of disperse dyes include benzene azo dyes (monoazo, disazo, etc.), heterocyclic azo dyes (thiazole azo, benzothiazole azo, quinoline azo, pyridine azo, imidazole azo, thiophene azo, etc.), anthraquinone dyes, and condensation dyes (quinophthaline, styryl, coumarin, etc.). These are commercially available as dyes with the prefix "Disperse". These may be used alone or in combination of two or more. In addition, the dyeing method may be a high-pressure liquid flow dyeing method, a jigger dyeing method, a thermosol continuous dyeing machine method, a sublimation printing method, or the like, without any particular limitation.

[0055] In this manner, the raised artificial leather of the present embodiment is obtained. The ultrafine fibers forming the nonwoven fabric contained in the raised artificial leather have a fineness of 0.15 to 0.5 dtex and a tensile strength of 6.5~8m By including a nonwoven fabric made of such ultrafine fiber bundles, a napped artificial leather is obtained that has an elegant napped appearance, high abrasion resistance, high friction resistance, and a soft feel.

[0056] The ultra-fine fibers that make up the nonwoven fabric are Degree 0.15~0 .5dte x and preferably 0.15~ The fineness is 0.3 dtex, and particularly preferably 0.15 to 0.25 dtex. If the fineness of the ultrafine fibers exceeds 0.5 dtex, it becomes difficult to obtain a beautiful napped appearance. If the fineness of the ultrafine fibers is too low, the abrasion resistance tends to deteriorate. The fineness is determined by taking a 3000x magnification image of a cross section of the napped artificial leather parallel to the thickness direction with a scanning electron microscope (SEM), and calculating the average value from 15 uniformly selected fiber diameters using the density of the resin forming the fibers.

[0057] In addition, the ultra-fine fibers that form the nonwoven fabric have a high tensile strength 6.5~8mN 。 Tensile strength of ultrafine fibers 6.5m If it is less than N, the ultrafine fibers on the nap surface will be too easily broken, and when the nap surface is rubbed against other articles, the nap will be easily shed, and the fluff will stain the other articles, resulting in a decrease in friction fastness (crocking fastness). 8m If it exceeds N, the ultrafine fibers on the napped surface will be too difficult to break, and during buffing to form the napped surface in the manufacturing process of the napped artificial leather, the napped ultrafine fibers will become long, making it difficult to obtain an elegant napped appearance, or the ultrafine fibers will be difficult to break when the napped surface is rubbed against another article, reducing the pilling resistance.

[0058] The tensile strength of the ultrafine fibers is the tensile strength of each ultrafine fiber that forms the raised artificial leather, and is the maximum stress when the ss curve per ultrafine fiber is measured in the tensile strength mode at a crosshead speed of 1 mm / min using a microautograph as described below, and is the average of the maximum stresses when five ultrafine fibers are measured.

[0059] In addition, the apparent density of the raised artificial leather is 0.3 8~0.48g / c m 3 in can be 、0 .4~0.48g / cm 3 Such an apparent density results in a raised artificial leather that is excellent in balance between a full feeling that does not break and a soft texture. 3 If the apparent density is less than 100%, the fabric will be easily broken due to its low density, and the fibers will be easily pulled out by rubbing the napped surface, making it difficult to obtain a beautiful napped appearance. If the apparent density of the napped artificial leather is too high, it will be difficult to obtain a soft texture.

[0060] The napped artificial leather of the present embodiment has a tensile strength A (mN) of the ultrafine fiber in the range of 6.5 to 8 mN, and an apparent density of the napped artificial leather of 0.38 to 0.48 g / cm3 The content ratio B of the polymer elastomer satisfies 3.125×A≦B. vinegar.

[0061] As shown in the examples described later, in relation to the tensile strength A (mN) of the ultrafine fiber in the range of 6.5 to 8 mN, the content ratio of the polymer elastomer satisfies the relational expression of 3.125×A≦B, and the apparent density of the raised nap artificial leather is 0.38 to 0.48 g / cm. 3 This makes it possible to obtain a napped artificial leather that is also highly resistant to pilling. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention should not be construed as being limited by the examples.

[0063] First, the evaluation methods used in the present examples will be summarized below.

[0064] <Fineness> The fineness was determined by measuring the cross-sectional area of ​​15 randomly selected ultrafine fibers observed in an image of a cross-section of the raised artificial leather in the thickness direction taken at 3000x with a scanning electron microscope (SEM), calculating the average cross-sectional area, and converting it into fineness from the density of each resin.

[0065] <Tensile strength> Shimadzu Techno Research Corporation measured the tensile strength of one ultrafine fiber by the following means. First, a mold 1 was prepared by cutting out a rectangular window W with a height of 1 mm in the center of cardboard 1 as shown in FIG. 1(a). Meanwhile, ultrafine fibers 2 with a length of 3 mm or more forming a nonwoven fabric were taken out from the cut artificial leather. Then, as shown in FIG. 1(b), the ultrafine fibers 2 were fixed to the mold 1 with adhesive 3 and adhesive tape 4 so that the ultrafine fibers 2 passed vertically through the center of the window W. Then, as shown in FIG. 1(c), one side frame C1 forming the window W of the mold 1 was cut with scissors. Then, in an atmosphere of 23°C and 50% RH, the upper and lower frames of the mold 1 were held by upper and lower chucks 11 and 12 of a micro autograph 10 (MST-X HR-U 0.5N kit (manufactured by Shimadzu Corporation)) with a chuck distance of 1 cm, as shown in FIG. 1(d). Then, as shown in Figures 1(e) and 1(f), the frame C2 on the other side forming the window W of the form 1 was also cut with scissors S. Then, as shown in Figure 1(g), an ss curve was created by measuring the stress when the crosshead 13 of the microautograph 10 was raised at a speed of 1 mm / min. The point at which the ss curve began to rise was taken as the zero point. The maximum stress in the ss curve was then determined, and the average value of the maximum stresses of the five ultrafine fibers was taken as the tensile strength.

[0066] <Polymer elastomer content> The weight (W1) of a piece of approximately 10 g of the raised artificial leather was measured. The piece was then immersed in dimethylformamide for a certain period of time, and the process of pressing was repeated to extract the polyurethane polymer elastomer. The nonwoven fabric remaining after extraction was then dried, and the weight (W2) of the dried nonwoven fabric was measured. The polymer elastomer content (B) was calculated from the formula: polymer elastomer content (B) = (W1-W2) / W1 x 100 (%).

[0067] <Apparent density> According to JIS L 1913, thickness (mm) and basis weight (g / cm 2 ) and from these values ​​the apparent density (g / cm 3 ) was calculated.

[0068] <Foaming rate of polymer elastomer (polyurethane)> Three images of an average location were taken at 300x magnification using a scanning electron microscope (SEM) at a section of 300μm from the surface of a cross section parallel to the thickness direction of the raised nap artificial leather, and each image was printed on A4 size paper. The printed paper was then placed on an overhead projector (OHP) sheet. The foamed area of ​​polyurethane, a polymeric elastomer, was then painted black and transferred onto the OHP sheet. At this time, voids containing fibers inside were considered to be voids formed when the sea component was removed from the islands-in-the-sea composite fiber, and were not recognized as foamed areas. Only independent voids not containing fibers inside were considered to be foamed areas. The pattern of the OHP sheet with the foamed areas painted black was then scanned with a scanner to form an image. The printed paper was placed on an OHP sheet, and the entire area where polyurethane was present, including the foamed area, was painted black on the OHP sheet to transfer the image. The OHP sheet with the entire area where polyurethane was present, including the foamed area, painted black was then scanned to form an image. The total area of ​​the blackened areas in all regions where polyurethane was present was calculated from the images obtained using an image processing device (image-pro plus, manufactured by Media Cybernetics Inc.) The total area of ​​the blackened areas in the foamed regions was also measured. Then, from the total area of ​​the black painted parts in all the regions where polyurethane exists and the total area of ​​the foamed parts in the black painted parts, Calculated using the formula: polyurethane foaming rate (%)=total area of ​​foamed parts in black painted areas / total area of ​​black painted areas in all areas where polyurethane is present×100.

[0069] <Intrinsic Viscosity of Resin Forming Ultrafine Fibers> The intrinsic viscosity of the resin forming the ultrafine fibers was determined by preparing a solution by dissolving the resin in a mixed solvent of phenol / tetrachloroethane (volume ratio 1 / 1) as the solvent, and measuring the viscosity of the solution at 30°C using an Ubbelohde viscometer (HRK-3 model, manufactured by Hayashi Seisakusho).

[0070] <Spinning draft> The extrusion speed A (g / min) of the molten resin extruded from one hole of the spinning nozzle, and the specific gravity B (g / cm 3 ), area of ​​one hole C (mm 2 ), and spinning speed D (m / min), and the calculated value was calculated using the following formula: Spinning draft = D / (A / B / C)

[0071] Clocking Crocking in the dry and wet states was measured using an Atlas Crockmeter CM-5 (manufactured by Atlas Electric Devices Co.). Dry crock fastness was measured as follows. A dry white cotton cloth was attached to a glass friction element, and the white cotton cloth attached to the friction element was brought into contact with the napped surface of the raised artificial leather under a load of 900 g and reciprocated 10 times. Then, the white cotton cloth was removed, Cellotape (registered trademark) was attached to the contaminated area, and a cylindrical load of 1.5 pounds was rolled back and forth once, after which the cellotape was peeled off from the white cotton cloth. Meanwhile, the crock fastness in wet conditions was measured as follows. A cotton cloth that had been soaked in distilled water and then had excess water removed was attached to a glass abrasive, and the cotton cloth attached to the abrasive was brought into contact with the napped surface of the raised artificial leather under a load of 900 g and moved back and forth 10 times. The cotton cloth was then removed and dried at 60°C or less, after which cellophane tape was attached to the contaminated area, a cylindrical load of 1.5 pounds was rolled back and forth once, and the cellophane tape was then peeled off from the cotton cloth. The crock fastness in dry and wet conditions was evaluated by judging the change in color of white cotton fabric using a staining gray scale (grade 5 to grade 1).

[0072] <Rubbing fastness> A white cloth conforming to JIS L 0803 was prepared using a Gakushin type friction tester, and the frictional element attached to it was rubbed against the surface of the test piece by moving it back and forth 30 times per minute over a distance of 10 cm under a load of 200 g, and 100 measurements were taken (conforming to JIS L 0849). The degree of color staining on the white cloth after 100 measurements was compared with the staining gray scale (conforming to JIS L 0805) and judged as dry conditions. For measurements under wet conditions, the white cloth was immersed in distilled water for 10 minutes or more according to JIS L 0849 9.1b, and then taken out, excess water was removed with filter paper, and measurements were taken in the same manner as for dry conditions using the cloth that was no longer dripping water, and the same judgment was made as for dry conditions.

[0073] <Pilling resistance> The test was conducted using a Martindale abrasion tester in accordance with JIS L 1096 (6.17.5E method, Martindale method) with a pressure load of 12 kPa and 5,000 abrasion cycles, and was graded according to the following criteria. 5: No change 4: A small amount of pilling with a maximum diameter of less than 1 mm occurred. 3: Pilling with a maximum diameter of 1 to 3 mm occurred. 2: Pilling with a maximum diameter of 3 to 5 mm occurred. 1: A large amount of pilling with a maximum diameter of more than 5 mm occurred.

[0074] <Wear loss> The wear loss of raised-pile artificial leather was measured according to JIS L 1096 (8.17.5E method, Martindale method) with a pressure load of 12 kPa (gf / cm 2 ) and abrasion tests were performed using a Martindale abrasion tester with 50,000 abrasion cycles to measure the amount of wear.

[0075] <Softness> The softness was measured using a softness tester (ST300 leather softness measuring device, manufactured by MSA Engineering Systems, UK). Specifically, a specified ring with a diameter of 25 mm was set in the lower holder of the device, and then the raised artificial leather was set in the lower holder. A metal pin (diameter 5 mm) fixed to the upper lever was pressed down toward the raised artificial leather. The upper lever was then pressed down to lock the upper lever, and the numerical value was measured at five different points, and the average value was read. The numerical value indicates the penetration depth, and the larger the numerical value, the more flexible the leather.

[0076] Texture The resulting raised nap artificial leather was bent, and the feel of stiffness and flexibility was evaluated according to the following criteria. A: It had a rich feel, was not easily broken, and had excellent flexibility. B: The texture was one or more of the following: lacking in solidity, prone to breaking, and hard.

[0077] <exterior> The appearance of the resulting raised nap artificial leather was judged by visual inspection and touch according to the following criteria. A: The fibers were finely dispersed and of uniform length, and the napped surface felt soft and smooth. B: The fibers were coarse and scattered, had uneven lengths, felt rough, and had a raised nap surface with no lighting.

[0078] [Example 1] A composition was prepared by adding 1.0 mass% of carbon black (CB) to polyethylene terephthalate (PET) with an intrinsic viscosity [η] = 0.67 (dl / g) and a melting point of 251°C, and preparing a resin for the sea part, polyethylene (PE) with a melt flow rate (MFR) of 25 (g / 10min, 190°C) was used as the resin for the island part. The composition was melt-spun at 285°C so that the ratio of sea part / island part was 35 / 65 (mass ratio). Specifically, the mixture was discharged from a spinneret with a nozzle diameter (hole diameter) of 0.40 mm at a single hole discharge rate of 1.5 g / min, and the ejector pressure was adjusted so that the spinning speed was 3450 m / min, and the long fibers were collected on a net. The mixture was spun at a spinning draft of 279 to obtain a web of islands-in-sea type composite fibers with a fineness of 4.3 dtex.

[0079] The obtained webs were then laminated to form a laminated web. The laminated web was then subjected to a 2020 P / cm stencil test using a 6-barb needle. 2 By needle punching at a punching density of 810g / m 2 An entangled fiber sheet was formed.

[0080] The entangled fiber sheet is then shrunk in hot water at 90°C, dried, and then heat pressed to produce a sheet with a basis weight of 912 g / m 2 , apparent density 0.389g / cm 3 Thus, a heat-shrinkable entangled fiber sheet having a thickness of 2.35 mm was obtained.

[0081] The heat-shrunk entangled fiber sheet was then impregnated with a DMF solution (solid content 18.5% by mass) of a polycarbonate-based non-yellowing polyurethane, which is a polymer elastomer and has a 100% modulus of 4.5 MPa, so that the ratio of the polymer elastomer to the napped artificial leather was 32% by mass, and the sheet was then immersed in a 30% DMF aqueous solution at 40°C to coagulate the polyurethane.

[0082] Next, the entangled fiber sheet to which the polyurethane was applied was immersed in toluene at 85°C while being nipped to dissolve and remove the PE, which is the sea component, and then dried. 2, apparent density 0.437g / cm 3 An artificial leather substrate was obtained that was a composite of polyurethane and a nonwoven fabric that was an entanglement of fiber bundles of ultrafine PET long fibers, with a thickness of 1.91 mm. Note that the ultrafine fiber nonwoven fabric was formed by impregnating polyurethane and then removing the sea component, so the ultrafine fibers inside the fiber bundles were not fixed together by polyurethane and were not restrained by polyurethane.

[0083] Then, after cutting the artificial leather substrate in half, a mixed solvent of DMF / cyclohexanone = 30 / 70 (weight ratio) was applied to the main surface to be the napped surface, and then dried to fix polyurethane to the ultrafine fibers of the surface layer. After that, #120 paper was used on the back surface of the cut in half, and #320 and #600 paper were used on the main surface to grind both sides, thereby finishing the artificial leather substrate with a napped surface. Then, the artificial leather substrate with the napped surface formed was dyed at 120°C under high pressure with a disperse dye to obtain a napped artificial leather with a suede-like napped surface. The napped artificial leather was then evaluated according to the above evaluation method. The results are shown in Table 1.

[0084] [Table 1]

[0085] [Examples 2 to 6, Comparative Examples 1 to 5] In Examples 2 to 5 and Comparative Examples 1, 2, 4, and 5, napped artificial leathers were obtained and evaluated in the same manner as in Example 1, except that the fineness and tensile strength of the ultrafine fibers were changed by setting the intrinsic viscosity and melting point of PET or the spinning conditions of the islands-in-sea type composite fibers as shown in Table 1. In Example 6, napped artificial leather was produced and evaluated in the same manner as in Example 1, except that the step of applying a mixed solvent of DMF / cyclohexanone = 30 / 70 (weight ratio) to the main surface that would become the napped surface and drying it was omitted. In Comparative Example 3, ultrafine fibers were directly spun to form an entangled body of ultrafine fibers, and the ultrafine fibers were bound to each other by a polymer elastomer. It should be noted that Example 4 is a reference example. The results are shown in Table 1.

[0086] [Comparative Example 6] Water-soluble polyvinyl alcohol resin (PVA; sea component) and isophthalic acid modified polyethylene terephthalate (island component) with a modification degree of 6 mol%, an intrinsic viscosity [η] = 0.59 (dl / g), a melting point of 240°C, were prepared. Then, they were extruded at a single hole output rate of 1.0 g / min from a melt composite spinning die (number of islands: 12 islands / fiber) at 260°C so that the sea component / island component ratio was 25 / 75 (mass ratio). Then, the ejector pressure was adjusted so that the spinning speed was 3300 m / min, and long fibers with a fineness of 3.0 dtex were collected on a net to obtain a web of islands-in-sea type composite fibers.

[0087] The obtained webs were cross-wrapped and stacked to obtain a stack, which was sprayed with an oil to prevent needle breakage.The stack was then entangled by needle punching using a needle with one barb and a needle count of 42 and a needle with six barbs and a needle count of 42 to obtain an entangled fiber sheet.

[0088] Next, the entangled fiber sheet was subjected to steam treatment under conditions of 110° C. and 23.5% RH, and then dried in an oven at 90 to 110° C., and then further subjected to heat pressing at 115° C. to obtain a heat-shrunk entangled fiber sheet.

[0089] Next, the heat-shrunk entangled fiber sheet was impregnated with an emulsion (solid content 40% by mass) of polycarbonate-based non-yellowing polyurethane, which is a polymeric elastomer and has a 100% modulus of 4.5 MPa, so that the content ratio of the polymeric elastomer to the raised artificial leather was 10% by mass, and then the polyurethane was dried and solidified. Next, the entangled fiber sheet to which the polyurethane was applied was immersed in hot water at 95°C for 10 minutes while being subjected to nip treatment and high-pressure water flow treatment to dissolve and remove the PVA, which is the sea component, and further dried. In this way, a fineness of 0.11 dtex and an apparent density of 0.435 / cm were obtained. 3 Thus, an artificial leather substrate was obtained which was a composite of polyurethane and a nonwoven fabric which was an entanglement of fiber bundles of ultrafine long fibers.

[0090] Next, the artificial leather substrate was cut in half, and a polyurethane DMF solution (5% solids) was applied to the main surface to be the napped surface, and then dried to fix the polyurethane to the ultrafine fibers of the surface layer. After that, #120 paper was used on the back surface of the cut in half, and #240, #320, and #600 paper were used on the main surface, and both sides were ground at a speed of 3.0 m / min and a rotation speed of 650 rpm to obtain an artificial leather substrate having a napped surface. The artificial leather substrate having the napped surface was then dyed at high pressure at 120°C using a disperse dye to obtain a napped artificial leather having a suede-like napped surface. The napped artificial leather was then evaluated according to the above evaluation method. The results are shown in Table 1.

[0091] [Comparative Example 7] An attempt was made to produce a napped artificial leather in the same manner as in Comparative Example 6, except that an isophthalic acid modified polyethylene terephthalate having a modification degree of 6 mol% and an intrinsic viscosity [η] = 0.67 (dl / g) and a melting point of 251°C was used instead of the isophthalic acid modified polyethylene terephthalate having a modification degree of 6 mol% and an intrinsic viscosity [η] = 0.59 (dl / g) and a melting point of 240°C in Comparative Example 6. However, the stability of the melt spinning was poor, and spinning was not possible.

[0092] Referring to Table 1, the napped artificial leathers of Examples 1 to 6, which contain a nonwoven fabric made of ultrafine fibers with a fineness of 0.5 dtex or less and a tensile strength of 6 to 9 mN and have a polymeric elastomer content of 16 to 40% by mass, were all rated as A in appearance and had an elegant napped appearance. In addition, the napped artificial leathers of Examples 1 to 6 had crocks of grade 4 or more in dry and grade 3-4 or more in wet, and had high abrasion fastness of grade 4-5 in dry and grade 3-4 or more in wet. In addition, the napped artificial leathers of Examples 1 to 6 had high abrasion resistance with an abrasion loss of 40 mg or less. In addition, the napped artificial leathers of Examples 1 to 6 had softness of 4.0 mm or more and had a soft texture. Thus, the napped artificial leathers of Examples 1 to 6, which consisted of ultrafine fibers having a fineness of 0.5 dtex or less and a tensile strength of 6 to 9 mN, contained 16 to 40 mass% of polymer elastomer, and in which the ultrafine fibers forming the fiber bundles in areas other than the surface layer were not restrained by the polymer elastomer, all had an elegant napped appearance, high abrasion resistance, high friction resistance, and a soft texture.

[0093] On the other hand, the raised artificial leather of Comparative Example 1, which includes a nonwoven fabric made of ultrafine fibers having a fineness of 0.5 dtex or less but a tensile strength of less than 6 mN, had abrasion loss of 65.2 mg, low abrasion resistance, wet crockage of grade 3, and wet friction fastness of grades 2-3, which were poor friction fastness. The raised artificial leather of Comparative Example 2, which includes a nonwoven fabric made of ultrafine fibers having a fineness of 0.5 dtex or less but a tensile strength of more than 9 mN, was rated as B in appearance and did not have a graceful raised appearance. The raised artificial leather of Comparative Example 3, which includes a nonwoven fabric made of ultrafine fibers having a fineness of more than 0.5 dtex and a tensile strength of 21 mN and in which the ultrafine fibers are bound by a polymeric elastomer, was also rated as B in appearance and did not have a graceful raised appearance. The raised artificial leather of Comparative Example 4, which contains a nonwoven fabric made of ultrafine fibers having a fineness of 0.5 dtex or less and a tensile strength of 6.5 mN, but contains 15% by mass of polymer elastomer, had an abrasion loss of 53.3 mg and a certain degree of abrasion resistance, but also had an appearance evaluation of B and did not have a graceful raised appearance. The raised artificial leather of Comparative Example 5, which contains a nonwoven fabric made of ultrafine fibers having a fineness of 0.5 dtex or less and a tensile strength of 6.4 mN, but contains 43% by mass of polymer elastomer, also had an appearance evaluation of B and did not have a graceful raised appearance. The raised artificial leather of Comparative Example 6, which contained a nonwoven fabric made of ultrafine fibers with a fineness of 0.5 dtex or less and a tensile strength of 5.3 mN and had a polymer elastomer ratio of 10% by mass, had an abrasion loss of 76 mg, low abrasion resistance, wet crockery of grade 1-2, and wet abrasion fastness of grade 1, indicating poor abrasion fastness.

[0094] [Example 7] A polyethylene (PE) with a melt flow rate (MFR) of 25 (g / 10 min, 190°C) was used as the sea component, and a polyethylene terephthalate (PET) with an intrinsic viscosity [η] of 0.67 (dl / g) and a melting point of 251°C was used as the island component to which 1.0% by mass of carbon black (CB) was added. Then, melt conjugate spinning was performed at 260°C so that the sea component / island component ratio was 35 / 65 (mass ratio). Specifically, the fibers were discharged from a spinneret with a hole diameter of 0.40 mm (number of islands: 12 islands / fiber) at a single hole discharge rate of 1.5 g / min, and the ejector pressure was adjusted so that the spinning speed was 3450 m / min, and the long fibers were collected on a net. Spinning was performed at a spinning draft of 279 to obtain a web of islands-in-sea type conjugate fibers with a fineness of 4.5 dtex.

[0095] The resulting web was then cut into a roll with a total basis weight of 600 g / m 2 The laminate was then cross-lapped to form a laminate web, and the stack was then laminated using a needle with one barb and a needle size of 42 and a needle with six barbs and a needle size of 42 to obtain a density of 4189 punches / cm. 2 The fabric is needle punched and entangled to give a weight of 840g / m 2 An entangled fiber sheet was formed.

[0096] The entangled fiber sheet was then shrunk in hot water at 90°C, dried in an oven at 90 to 110°C, and pressed with a roll to produce a sheet with a basis weight of 940 g / m 2 , apparent density 0.40g / cm 3 Thus, a heat-shrinkable entangled web sheet having a thickness of 2.35 mm was obtained.

[0097] The heat-shrunk entangled fiber sheet was then impregnated with a DMF solution (solid content 18.5%) of a polycarbonate-based non-yellowing polyurethane, which is a polymer elastomer with a 100% modulus of 3.2 MPa, so that the polyurethane content relative to the napped artificial leather was 32 mass%, and then the sheet was immersed in a 30% DMF aqueous solution at 40°C to coagulate the polyurethane.

[0098] Next, the entangled fiber sheet to which the polyurethane was applied was immersed in toluene at 90°C while being nipped to dissolve and remove the PE, which is the sea component, and then dried. 2 , apparent density 0.458g / cm 3 An artificial leather substrate was obtained that was a composite of polyurethane and a nonwoven fabric that was an entanglement of fiber bundles of ultrafine PET long fibers, with a thickness of 1.77 mm. Note that the ultrafine fiber nonwoven fabric was formed by impregnating polyurethane and then removing the sea component, so the ultrafine fibers inside the fiber bundles were not fixed together with polyurethane and the ultrafine fibers were not restrained.

[0099] Then, after cutting the artificial leather substrate in half, a mixed solvent of DMF / cyclohexanone = 30 / 70 (weight ratio) was applied to the main surface to be the napped surface, and then dried to fix polyurethane to the ultrafine fibers of the surface layer. After that, the back side of the cut in half was ground with #120 paper, and the main surface was ground with #240, #320, and #600 paper, to form an artificial leather substrate with a napped surface. The artificial leather substrate with the napped surface was then dyed with a disperse dye at 120°C under high pressure to obtain a napped artificial leather with a suede-like napped surface. The napped artificial leather was then evaluated according to the above evaluation method. The results are shown in Table 2.

[0100] [Table 2]

[0101] [Examples 8 to 22, 24 to 33, Comparative Examples 8 to 10] In Examples 8 to 19, 21 to 22, 24 to 33 and Comparative Examples 8 to 10, napped artificial leathers were obtained and evaluated in the same manner as in Example 7, except that the intrinsic viscosity, melting point, and CB content of PET, or the spinning conditions of islands-in-sea type composite fibers, the content of polymer elastomer, and the presence or absence of application and drying of a mixed solvent of DMF / cyclohexanone were set as shown in Table 2 or the following Table 3. In Example 20, napped artificial leathers were obtained and evaluated in the same manner as in Example 7, except that the raw staple cotton of the islands-in-sea type composite fibers obtained by crimping and cutting the melt-spun islands-in-sea type composite fibers was carded to form a short fiber web. It should be noted that Examples 21, 22, 24 to 27, and 28 to 33 are reference examples. The evaluation results are shown in Table 2 or Table 3 below.

[0102] [Table 3]

[0103] Example 2 3 (reference example), Comparative Example 11 In Example 23 and Comparative Example 11, raised-pile artificial leathers were obtained and evaluated in the same manner as in Comparative Example 6, except that the intrinsic viscosity of PET, the spinning conditions for islands-in-the-sea type composite fibers, the content of polymer elastomer, and the application and drying of a mixed solvent of DMF / cyclohexanone were set as shown in Table 3. The evaluation results are shown in Table 3.

[0104] Fig. 2 shows a graph plotting the content ratio (B) of polymer elastomer against the tensile strength (A) of ultrafine fibers contained in the napped artificial leather shown in Table 2. Fig. 3 shows a graph plotting the content ratio (B) of polymer elastomer against the tensile strength (A) of ultrafine fibers contained in the napped artificial leather shown in Table 3.

[0105] Referring to Table 2, the napped artificial leathers obtained in Examples 7 to 20 had tensile strength (A) in the range of 6.5 to 8 mN, and the content ratio (B)% of the polymeric elastomer satisfied 3.125×(A)≦(B), as shown in Fig. 2. Referring to Table 2, these napped artificial leathers were napped artificial leathers that had high pilling resistance of grade 4 or higher, high abrasion resistance with an abrasion loss of 40 mg or less, a soft feel with a softness of 3.7 mm or more, and an elegant napped appearance with finely dispersed fibers of uniform length and a napped surface with a soft and smooth feel.

[0106] Also, referring to Table 3, Examples 21, 22, 24-27, 28-33 have tensile strength (A) in the range of 6.5-8 mN as shown in Fig. 3, and the content ratio (B)% of the polymeric elastomer does not satisfy 3.125 x (A) <= (B). Referring to Table 3, these raised artificial leathers had slightly low pilling resistance or abrasion resistance. Also, Example 23, which has a high apparent density, had a hard feel.

Claims

1. A napped artificial leather comprising a nonwoven fabric which is an entanglement of ultrafine fibers and a polymeric elastomer applied to the nonwoven fabric, and having at least one napped surface in which the ultrafine fibers are napped, The ultrafine fibers have a fineness of 0.15 to 0.5 dtex and a tensile strength A (mN) of 6.5 to 8 mN, and a plurality of the ultrafine fibers form a fiber bundle; In the region other than the surface layer portion, the ultrafine fibers forming the fiber bundle are not bound by the polymer elastomer, The content ratio B (mass%) of the polymer elastomer satisfies the formula 3.125×A≦B≦40 mass%, A raised artificial leather having an apparent density of 0.38 to 0.48 g / cm 3 .

2. 2. The napped artificial leather according to claim 1, wherein the polymeric elastomer is a solvent-based polyurethane.

3. 3. The napped artificial leather according to claim 1, wherein the foaming rate of the polymeric elastomer is 0 to 5% by mass.

4. 4. The napped artificial leather according to claim 1, wherein a part of the polymeric elastomer present in the surface layer portion is fixed to the vicinity of the roots of the napped ultrafine fibers.

5. 5. The napped artificial leather according to claim 1, wherein the ultrafine fibers are ultrafine fibers formed by dissolving and removing a sea component from islands-in-sea type composite fibers with an organic solvent.

6. 6. The napped artificial leather according to claim 1, wherein the nonwoven fabric is a spunbonded nonwoven fabric containing the ultrafine fibers which are long fibers.

Citation Information

Patent Citations

  • Suguretahikakuyofuaino shiitojobutsushitsuno seizoho

    JP1976075178A

  • Production of flexible artificial leather having high abrasion resistance

    JP1994316877A

  • Production of napped sheet having excellent abrasion resistance

    JP2001081677A

  • Leathery sheetlike material and method for producing the same

    JP2004197232A

  • Artificial leather and method for producing the same

    JP2007100249A